KORELASI ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI SDN LENGAHJAYA 02 KABUPATEN BEKASI - Siti Humairoh; Hesti Widiastuti; Yulistina Nur DS; Harmawati; Imas Indah Mutiara (Postgraduate, University of Mataram, 2024)
The purpose of this study is to determine: the learning motivation of Grade IV primary school students; the learning outcomes of Grade V primary school students in science; and the correlation between learning motivation and learning outcomes of Grade V primary school students in science. This research is a type of quantitative research with a descriptive correlational design. The population used in this study were all fourth-grade students from SDN Lengahjaya 02, a total of 63 students. The sampling technique was purposive sampling with a large sample size of 39. Data were collected using a research instrument in the form of a questionnaire. Of the 30 items tested, there were 28 valid questions. The data analysis technique used was product-moment correlation. The results showed that the average learning motivation of the students was 74.1 and the average learning outcome of the students was 71.5. There is a significant correlation between learning motivation and science learning outcome of the 5th grade students of SDN Lengahjaya 02 with a correlation test value of 0.323 and a low coefficient value.